Permohonan Praperadilan Tentang Penetapan Tersangka yang Berstatus Daftar Pencarian Orang (DPO) di Pengadilan Negeri Denpasar - Dewa Gede Adi Kesumayuda; Anak Agung Sagung Laksmi Dewi; Kade Richa Mulyawati (Jurnal Interpretasi Hukum, 2025)
A pretrial application filed by a suspect who has the status of a Wanted Person List (DPO). This raises problems, because it is not in line with SEMA Number 1 of 2018.So that the formulation of the problem, 1) What is the procedure for pretrial applications filed by suspects with DPO status?, 2) What are the obstacles in the pretrial process filed by suspects with DPO status at the Denpasar District Court? The purpose of this study is to analyze and understand the procedure for pretrial applications filed by suspects with DPO status, as well as the obstacles. The method used is an empirical method. The pretrial application procedure submitted by a suspect with DPO status is the same as the pretrial application procedure in general, but after that the application is rejected in line with the regulations. The obstacle that occurs is that the suspect is a person with DPO status in the sense that the suspect cannot fulfill attendance. The effort made was to call back the suspect even though the suspect was still a DPO. With suggestions that a more complex policy be formed.